UPAYA PENINGKATAN HASIL BELAJAR MENGHAFAL JUZ 30 MELALUI METODE DRILL PADA PROGRAM HAFALAN AL QURAN SISWA MAN KOTA BANJARBARU - ANWAR ZARKASI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
Against the background of the unsatisfactory results of the Al-Quran memorization program for class XI IIK MAN Banjarbaru City students, which was caused by an ineffective learning process, this research was made with the aim of increasing student motivation in memorizing; improve students' ability to memorize; and improve students' ability to maintain memorization of verses of the Koran, especially verses that have been determined as graduation requirements. This research is a Classroom Action Research (CAR). Efforts to collect data in this study using test and non-test techniques. For test techniques, the data collection tool is in the form of an assessment when the teacher gives questions to students during the research cycle. For the non-test technique, the data collection tool is in the form of an observation sheet which is carried out to determine the condition of students in memorizing learning. Observations were also made of the teacher in carrying out the learning process. Data on student learning outcomes are obtained from the evaluation results at the end of each cycle. The results of the study prove that the drill model can improve students' ability to memorize surah an-Naba' verses 1 to 10 students of Class XI IIK MAN Banjarbaru City which can be seen from the increase in several aspects related to the activity of students memorizing verses of the Koran which includes the average score of the activity students who are relevant to learning experience an increase in cycle II of 6.52%. On the other hand, the average score of student activities that were less relevant to learning decreased from cycle I to cycle II by -13.04%. and the average score of students' ability to memorize surah an-Naba 'verse 1 to 10 has increased by 13.04, as well as about the completeness of student learning which has increased in cycles of 26.08%. ABSTRAKDilatarbelakangi oleh hasil program menghafal al Quran siswa kelas XI IIK MAN Kota Banjarbaru yang tidak memuaskan, yang disebabkan oleh proses pembelajaran yang tidak efektif maka dibuatlah penelitian ini dengan tujuan sebagai upaya meningkatkan motivasi siswa dalam menghafal; meningkatkan kemampuan siswa dalam menghafal; dan meningkatkan kemampuan siswa dalam mempertahankan hafalan ayat al-Qur’an, terutama ayat ayat yang sudah ditentukan sebagai syarat kelulusan. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Upaya pengumpulan data dalam penelitian ini menggunakan teknik tes dan nontes. Untuk teknik tes, alat pengumpul data berupa penilaian saat guru memberi pertanyaan pada siswa saat siklus penelitian berlangsung. Untuk teknik nontes, alat pengumpul data berupa lembar observasi yang dilakukan untuk mengetahui kondisi siswa di dalam belajar menghafal. Observasi juga dilakukan terhadap guru dalam melaksanakan proses pembelajaran. Data hasil belajar siswa diperoleh dari hasil evaluasi disetiap akhir siklus. Hasil penelitian membuktikan bahwa model drill dapat meningkatkan kemampuan siswa dalam menghafal surah an-Naba’ ayat 1 sd 10 siswa Kelas XI IIK MAN Kota Banjarbaru yang terlihat dari adanya peningkatan beberapa aspek berkaitan dengan aktivitas siswa menghafal ayat al Quran yang meliputi skor rata-rata aktivitas siswa yang relevan dengan pembelajaran mengalami peningkatan pada siklus II sebesar 6.52%. Sebaliknya skor rata-rata aktivitas siswa yang kurang relevan dengan pembelajaran mengalami penurunan dari siklus I sampai siklus II sebesar -13.04%. dan skor rata-rata kemampuan siswa menghafal surah an-Naba’ ayat 1 sd 10 mengalami peningkatan sebesar 13.04, begitu juga tentang kenuntasan belajar siswa yang mengalami kenaikan pada siklus sebesar 26.08%.